A coating for aviation titanium forgings and its treatment process

By applying a coating composed of an inner coating and an outer coating on aviation titanium forgings, combined with the use of intermediate coatings, the problem of titanium alloys being easily oxidized and burned at high temperatures is solved, significantly improving its oxidation and flame retardant properties, ensuring safe application in higher temperature environments.

CN119391303BActive Publication Date: 2025-04-04BAOJI BAOYE TITANIUM NICKEL IND
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411974646.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-04
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

Titanium alloys are prone to oxidation and combustion at medium and even high temperatures. The prior art is difficult to effectively prevent oxidation and combustion, which limits its application in higher temperature environments.

Method used

Aeronautical titanium forging coating consisting of an inner coating and an outer coating is used. The inner coating contains TiO2, B4C, B2O3, MgO, and the outer coating contains B2O3, Al2O3, SiO2, KOH. By changing the composition and dosage ratio, an intermediate coating is further added to improve oxidation resistance and flame retardant properties.

Benefits of technology

It significantly improves the oxidation and flame retardant properties of titanium alloy, extends the wear resistance and corrosion resistance of the coating, improves the high-temperature oxidation resistance, and effectively avoids the occurrence of titanium fire accidents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses an aviation titanium forging coating and a treatment process thereof, belonging to the field of aerospace technology, comprising an inner coating and an outer coating, wherein the inner coating is composed of the following raw materials by mass percentage: inner coating: TiO2 45%-50%, B4C 6%-11%, B2O3 28%-34%, MgO 6%-10%, and the sum of the mass percentages of the above raw materials is 100%; the outer coating is composed of the following raw materials by mass percentage: outer coating: B2O3 0.7%-2.0%, Al2O3 26%-36%, SiO2 30%-32%, KOH 23.3%-30%, TiB2 10-15%, and the sum of the mass percentages of the above raw materials is 100%. By changing the composition and dosage ratio of the outer coating and the inner coating, the anti-oxidation and flame retardant effects of the titanium alloy are significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of aerospace technology and relates to an aviation titanium forging coating. The invention also relates to a method for treating the aviation titanium forging by using the coating. Background Art

[0002] Aviation titanium forgings refer to titanium alloy forging products used in the aerospace field. They usually have the characteristics of high strength, low density, good corrosion resistance and weldability. Titanium alloys have been widely used in important load-bearing parts of aircraft and aircraft engines due to their excellent comprehensive performance. According to statistics, the weight ratio of titanium alloys used in foreign aircraft has reached about 30%. TC4 titanium alloy (Ti-6Al-4V) is one of the important materials, which is highly favored due to its lightweight advantages. Its density is about 4.43g / cm³, which is about 40% lower than that of heavy steel. The tensile strength of TC4 titanium alloy can reach 895-1050MPa, especially under high temperature conditions.

[0003] However, the oxide film formed on titanium alloy at medium or even high temperature is porous TiO2, which cannot effectively resist the inward diffusion of oxygen atoms. Therefore, there is a need for antioxidant protection for titanium alloy.

[0004] At the same time, since the ignition point of titanium alloy is lower than its melting point, high-speed moving titanium alloy parts may ignite the titanium alloy due to frictional heat and cause titanium fire accidents, which seriously endangers the safe use of aerospace vehicles. Therefore, there is also a need for flame retardancy for titanium alloy.

[0005] CN102675952B is an invention patent applied for by the applicant in 2012. The patented method can avoid the oxidation of titanium alloy to a certain extent, but there are still problems of oxidation and ineffective flame retardancy during long-term use.

[0006] However, titanium alloys are prone to oxidation and combustion at high temperatures, which limits their application in higher temperature environments. Therefore, it is particularly important to develop effective coating technology to improve its anti-oxidation and flame retardant properties. Summary of the invention

[0007] In order to improve the anti-oxidation and flame retardant properties of aviation titanium forgings, the purpose of the present application is to provide an aviation titanium forging coating and a treatment process thereof, which can effectively achieve the anti-oxidation and flame retardant effects on titanium alloys.

[0008] The present invention provides the following technical solution: an aviation titanium forging coating, comprising an inner coating and an outer coating, wherein the inner coating is composed of the following raw materials in terms of mass percentage:

[0009] Inner coating: TiO2 45%-50%, B4C 6%-11%, B2O3 28%-34%, MgO 6%-10%, the total mass percentage of the above raw materials is 100%;

[0010] The outer coating layer is composed of the following raw materials in terms of mass percentage:

[0011] Outer coating: B2O3 0.7%-2.0%, Al2O3 26%-36%, SiO2 30%-32%, KOH 23.3%-30%, TiB2 10-15%, the total mass percentage of the above raw materials is 100%.

[0012] Preferably, it also includes an intermediate coating, which is rare earth-modified regranulated nanostructured Al2O3 and TiO2.

[0013] Preferably, ZrO2 and CeO2 are used as composite additives for synergistic modification, wherein the mass ratio of Al2O3, TiO2, ZrO2 and CeO2 is 87:13:2:2.

[0014] Preferably, the inner coating layer is composed of the following raw materials in terms of mass percentage:

[0015] TiO245%, B4C 11%, B2O334%, MgO 10%;

[0016] The outer coating layer is composed of the following raw materials in terms of mass percentage:

[0017] B2O30.7%, Al2O336%, SiO230%, KOH 23.3%, TiB210%.

[0018] Preferably, the inner coating layer is composed of the following raw materials in terms of mass percentage:

[0019] TiO245%, B4C 11%, B2O334%, MgO 10%;

[0020] The intermediate coating is rare earth modified regranulated nanostructured Al2O3 and TiO2, wherein ZrO2 and CeO2 are used as composite additives for synergistic modification, wherein the mass ratio of Al2O3, TiO2, ZrO2 and CeO2 is: 87:13:2:2;

[0021] The outer coating layer is composed of the following raw materials in terms of mass percentage:

[0022] B2O30.7%, Al2O336%, SiO230%, KOH 23.3%, TiB210%.

[0023] Preferably, the coating treatment process includes: cleaning the aviation titanium forging and drying; weighing TiO245%, B4C 11%, B2O334%, and MgO 10% according to mass percentage; then mixing the raw materials and ball milling them on a ball mill to form a powdery mixture with a particle size of 350-450 mesh; then adding varnish and banana water, stirring to a viscosity of 50-80 centipoise to prepare an inner coating paint, and then brushing the inner coating paint on the surface of the aviation titanium forging with a thickness of 0.3 mm and naturally air-drying; then weighing B2O30.7%, Al2O336%, SiO230%, KOH 23.3%, and TiB210% according to mass percentage, and then mixing them, ball milling them on a ball mill to form a powdery mixture with a particle size of 350-450 mesh; then adding varnish and banana water, stirring to a viscosity of 50-80 centipoise, brushing them on the outer surface of the inner coating with a thickness of 0.3 mm, and naturally air-drying, thereby completing the treatment of the aviation titanium forging.

[0024] Preferably, another treatment process of the coating includes: cleaning the aviation titanium forging and drying; weighing TiO245%, B4C 11%, B2O334%, MgO 10%; then mix the raw materials, and ball-mill them on a ball mill to form a powdery mixture with a particle size of 350-450 mesh; then add varnish and banana water, stir to a viscosity of 50-80 centipoise to prepare an inner coating, and then brush the inner coating on the surface of the aviation titanium forging to a thickness of 0.3mm, and air dry naturally; weigh Al2O3, TiO2, ZrO2 and CeO2 according to a mass ratio of 87:13:2:2, ball-mill them on a ball mill to form a powdery mixture, spray-dry the ball-milled powder to form a plasma-sprayed powder form, heat-treat and plasma-treat the spray-dried powder respectively, and the particle size is 20-50 microns, and finally plasma spray the aviation titanium forging brushed with the inner coating, with a spray thickness of 0.3mm, and air dry naturally to form an intermediate coating; then weigh B2O30.7%, Al2O336%, SiO230%, KOH according to mass percentage 23.3%, TiB210%, then mix and ball-mill on a ball mill to form a powdery mixture with a particle size of 350-450 mesh; then add varnish and banana water, stir to a viscosity of 50-80 centipoise, brush on the outer surface of the intermediate coating with a thickness of 0.3mm, and air-dry naturally to complete the treatment of aviation titanium forgings.

[0025] The beneficial effects of the present invention are:

[0026] By changing the composition and dosage ratio of the outer coating and the inner coating, the anti-oxidation and flame retardant effects of the titanium alloy are improved to a certain extent, and further adding the intermediate coating can significantly improve the anti-oxidation and flame retardant effects of the titanium alloy;

[0027] In the inner coating, the proportion of B2O3 is increased to about 30% to improve the antioxidant performance and improve the thermal expansion coefficient matching; the component K2O·SiO2 is omitted, and the amount of TiO2 is appropriately increased. This is based on our daily experiments that we found that the protective effect of K2O·SiO2 in the coating combination is not very good;

[0028] The role of the outer coating is to prevent pollution caused by chemical reactions with oxygen in the air. Therefore, the outer coating directly affects the anti-oxidation and flame retardant effects.

[0029] The current outer coating composition of 0.7% B2O3, 46% Al2O3, 30% SiO2, and 23.3% KOH has been found to have a long-term use, and the wear resistance, corrosion resistance, and high-temperature oxidation resistance of the above coating need to be improved. Therefore, after repeated tests, titanium diboride (TiB2) was added to improve the performance of the outer coating.

[0030] The intermediate coating is: rare earth modified regranulated nanostructured Al2O3 and TiO2, which has the following functions:

[0031] 1. Improve coating performance: Rare earth modification can improve the microhardness of Al2O3 and TiO2 coatings, reduce friction coefficient and improve wear resistance. This is because the addition of rare earth elements can change the microstructure of the coating, forming a bimodal microstructure, including a completely melted area and a partially melted area, thereby improving the performance of the coating.

[0032] 2. Antioxidation performance: The addition of rare earth elements such as CeO2 can improve the antioxidant performance of composite materials. An appropriate amount of CeO2 can stabilize ZrO2, thereby improving the material's resistance to high temperature oxidation. DETAILED DESCRIPTION

[0033] The present invention is further described below by specific examples and comparative examples. However, it should be understood that these examples and comparative examples are only used for more detailed and specific description and should not be construed as limiting the present invention in any form.

[0034] Example 1

[0035] An aviation titanium forging coating, characterized in that it is divided into two layers: an inner coating and an outer coating:

[0036] Inner coating: TiO2 45%, B4C 11%, B2O3 34%, MgO 10%;

[0037] External coating, B2O30.7%, Al2O346%, SiO230%, KOH 23.3%;

[0038] The treatment process is as follows: cleaning the aviation titanium forgings and drying; weighing TiO2 45%, B4C 11%, B2O3 34%, and MgO 10% according to mass percentage; then mixing the raw materials, and ball milling them on a ball mill to form a powdery mixture with a particle size of 350-450 meshes; then adding varnish and banana water, stirring to a viscosity of 50-80 centipoises to prepare an inner coating, and then brushing the inner coating on the surface of the aviation titanium forgings with a thickness of 0.3 mm, and naturally air drying; then weighing 0.7% B2O3, 46% Al2O3, 30% SiO2, and 23.3% KOH according to mass percentage, and then mixing them, ball milling them on a ball mill to form a powdery mixture with a particle size of 350-450 meshes; then adding varnish and banana water, stirring to a viscosity of 50-80 centipoises, brushing them on the outer surface of the inner coating with a thickness of 0.3 mm, and naturally air drying, thus completing the treatment of the aviation titanium forgings.

[0039] Example 2

[0040] An aviation titanium forging coating, characterized in that it is divided into two layers: an inner coating and an outer coating:

[0041] Inner coating: TiO242%, B4C 6%, K2O·SiO224%, B2O322%, MgO 6%;

[0042] External coating, B2O3 0.7%, Al2O3 36%, SiO2 30%, KOH 23.3%, TiB2 10%;

[0043] The treatment process is as follows: cleaning the aviation titanium forgings and drying; weighing TiO2 42%, B4C 6%, K2O·SiO2 24%, B2O3 22%, and MgO 6% according to mass percentage; then mixing the raw materials, ball milling them on a ball mill to form a powdery mixture with a particle size of 350-450 meshes; then adding varnish and banana water, stirring to a viscosity of 50-80 centipoises to prepare an inner coating, and then brushing the inner coating on the surface of the aviation titanium forgings with a thickness of 0.3 mm, and naturally air drying; then weighing B2O3 0.7%, Al2O3 36%, SiO2 30%, KOH 23.3%, and TiB2 10% according to mass percentage, and then mixing them, ball milling them on a ball mill to form a powdery mixture with a particle size of 350-450 meshes; then adding varnish and banana water, stirring to a viscosity of 50-80 centipoises, brushing them on the outer surface of the inner coating with a thickness of 0.3 mm, and naturally air drying, and the aviation titanium forgings are completed.

[0044] Example 3

[0045] An aviation titanium forging coating, characterized in that it is divided into two layers: an inner coating and an outer coating:

[0046] Inner coating: TiO2 45%, B4C 11%, B2O3 34%, MgO 10%;

[0047] External coating, B2O30.7%, Al2O336%, SiO230%, KOH 23.3%, TiB210%;

[0048] The treatment process is as follows: cleaning the aviation titanium forgings and drying; weighing TiO245%, B4C 11%, B2O334%, and MgO 10% according to mass percentage; then mixing the raw materials and ball milling them on a ball mill to form a powdery mixture with a particle size of 350-450 meshes; then adding varnish and banana water, stirring to a viscosity of 50-80 centipoise to prepare an inner coating, and then brushing the inner coating on the surface of the aviation titanium forgings with a thickness of 0.3 mm, and naturally air drying; then weighing B2O30.7%, Al2O336%, SiO230%, KOH 23.3%, and TiB210% according to mass percentage, and then mixing them, ball milling them on a ball mill to form a powdery mixture with a particle size of 350-450 meshes; then adding varnish and banana water, stirring to a viscosity of 50-80 centipoise, brushing on the outer surface of the inner coating with a thickness of 0.3 mm, and naturally air drying to complete the aviation titanium forgings.

[0049] Example 4

[0050] An aviation titanium forging coating, characterized in that it is divided into three layers: an inner coating, an intermediate coating and an outer coating:

[0051] Inner coating: TiO2 45%, B4C 11%, B2O3 34%, MgO 10%;

[0052] Intermediate coating: rare earth modified regranulated nanostructured Al2O3 and TiO2;

[0053] External coating, B2O30.7%, Al2O336%, SiO230%, KOH 23.3%, TiB210%;

[0054] The treatment process is as follows: clean the aviation titanium forgings, dry them; weigh TiO245%, B4C 11%, B2O334%, MgO 10%; then mix the raw materials, and ball-mill them on a ball mill to form a powdery mixture with a particle size of 350-450 mesh; then add varnish and banana water, stir to a viscosity of 50-80 centipoise to prepare an inner coating, and then brush the inner coating on the surface of the aviation titanium forging to a thickness of 0.3mm, and air dry naturally; weigh Al2O3, TiO2, ZrO2 and CeO2 according to a mass ratio of 87:13:2:2, ball-mill them on a ball mill to form a powdery mixture, spray-dry the ball-milled powder to form a plasma-sprayed powder form, heat-treat and plasma-treat the spray-dried powder respectively, and the particle size is 20-50 microns, and finally plasma spray the aviation titanium forging brushed with the inner coating, with a spray thickness of 0.3mm, and air dry naturally to form an intermediate coating; then weigh B2O30.7%, Al2O336%, SiO230%, KOH according to mass percentage 23.3%, TiB210%, then mix and ball-mill on a ball mill to form a powdery mixture with a particle size of 350-450 mesh; then add varnish and banana water, stir to a viscosity of 50-80 centipoise, brush on the outer surface of the intermediate coating with a thickness of 0.3mm, and air-dry naturally to complete the treatment of aviation titanium forgings.

[0055] Comparison example

[0056] Example 1 in the patent application number CN102675952B filed by the applicant in 2012: Cleaning the TC4 titanium plate blank; weighing 42% TiO2, 6% B4C, 24% K2O·SiO2, 22% B2O3, and 6% MgO according to mass percentage; then mixing the raw materials and ball milling them on a ball mill to form a powdery mixture with a particle size of 350-450 mesh; then adding varnish and banana water, stirring to a suitable viscosity (50-80 centipoise) to prepare an inner coating, and then brushing the inner coating on the surface of the TC4 titanium plate blank The surface is coated with 0.3mm thick and air-dried naturally; then, 0.7% B2O3, 46% Al2O3, 30% SiO2 and 23.3% KOH are weighed according to the mass percentage, and then mixed and ball-milled on a ball mill to form a powdery mixture with a particle size of 350-450 mesh; then varnish and banana water are added, stirred to a suitable viscosity (50-80 centipoise), and brushed on the outer surface of the inner coating with a thickness of 0.3mm and air-dried naturally to complete the treatment of the TC4 titanium plate.

[0057] Effect experiment 1: Antioxidant properties

[0058] Experimental method: 6 pieces of titanium alloy with a size of 1 cm×1 cm and a thickness of 2 mm were prepared, 5 of which were treated according to the treatment processes of Examples 1-4 and the control group, and the other piece was not treated at all as the reference group. The temperature of 900°C was selected for the cyclic oxidation test, and the sample was placed in a high temperature furnace for 40 hours.

[0059] Determination method: Before and after oxidation, use a balance (electronic balance with an accuracy of 0.0001g) to measure the mass change of the sample and calculate the mass change ratio. The experimental results are shown in Table 1.

[0060] Table 1

[0061]

[0062] From the above data we can see that:

[0063] 1. Compared with the baseline group, the control group (Example 1 in CN102675952B) has shown excellent antioxidant performance, in which the mass change ratio is reduced from 0.518% to 0.251%.

[0064] 2. Compared with the control group, Example 1 mainly adjusts the components and proportions of the inner coating. First, the adjustment further reduces the oxidized mass proportion. However, since the inner coating is adjusted and the outer coating is not adjusted, its antioxidant performance does not show a significant decrease, but only decreases to 0.208%, that is, the current outer coating still has the defect of being oxidized.

[0065] 3. Compared with the control group, Example 2 mainly adjusts the components and proportions of the outer coating. It can be seen that the antioxidant performance of this adjustment has been further improved compared with Example 1, and the mass change is 0.166%, which fully demonstrates that the outer coating directly affects the antioxidant effect.

[0066] 4. Compared with the control group, in Example 3, the components and proportions were adjusted in both the inner coating and the outer coating. It can be seen that the above adjustments have significantly improved the antioxidant properties of the titanium alloy, and the mass change is only 0.121%. This also shows that the adjustment of the above components and dosages has achieved unexpected technical effects.

[0067] 5. Compared with Example 3, Example 4 further adds an intermediate coating on the basis of Example 3. It can be seen that its antioxidant performance is improved to a mass change of only 0.087% compared with Example 3. It can be shown that the rare earth modified regranulated nanostructured Al2O3 and TiO2 can further improve the antioxidant performance of titanium alloy.

[0068] Effect experiment 2: Flame retardant performance test of flamethrower

[0069] Sample preparation: Prepare 3 titanium forging substrates of the same size (1 cm × 1 cm, thickness 2 mm) and ensure that the surface is clean and free of oil stains.

[0070] The titanium forging substrate coating was prepared using the methods of the control example, example 3 and example 4 respectively.

[0071] Flame spray gun settings: The flame temperature of the flame spray gun is 1300 degrees Celsius; the flame spray gun is 30 cm away from the test sample, and the ignition time is set to 5 seconds.

[0072] The time for the above coating to be ignited is shown in Table 2 below:

[0073] Table 2

[0074]

[0075] For the above data, the ignition time of the control group is 9.2s, which is a relatively conventional coating ignition time in the industry. On the basis of the control group, the flame retardant time of Example 3 and Example 4 is further extended, that is, the products prepared by the present invention have very excellent flame retardant properties.

[0076] The above-described embodiments are exemplary and are not intended to limit the invention which is further described in the claims.

Claims

1. An aviation titanium forging coating, characterized in that: It includes an inner coating and an outer coating, wherein the inner coating is composed of the following raw materials in terms of mass percentage: Inner coating: TiO2 45%, B4C 11%, B2O3 34%, MgO 10%; The outer coating layer is composed of the following raw materials in terms of mass percentage: External coating: B2O3 0.7%-2.0%, Al2O3 26%-36%, SiO2 30%-32%, KOH 23.3%-30%, TiB2 10-15%, the total mass percentage of the above raw materials is 100%; It also includes an intermediate coating, and the preparation method of the intermediate coating is as follows: Al2O3, TiO2, ZrO2 and CeO2 are weighed according to a mass ratio of 87:13:2:2, and ball-milled on a ball mill to form a powdery mixture, spray-dried the ball-milled powder to form a plasma-sprayed powder form, and the spray-dried powder is heat-treated and plasma-treated respectively, and the particle size is 20 to 50 microns.

2. The aviation titanium forging coating according to claim 1, characterized in that: The outer coating layer is composed of the following raw materials in terms of mass percentage: B2O30.7%, Al2O336%, SiO230%, KOH 23.3%, TiB2 10%.

3. A treatment process for aviation titanium forging coating according to claim 2, characterized in that: The following steps are involved: Clean the aviation titanium forgings and dry them; weigh TiO245%, B4C 11%, B2O334%, MgO according to mass percentage. 10%; then mix the raw materials, ball-mill them on a ball mill to form a powdery mixture with a particle size of 350-450 mesh; then add varnish and banana water, stir to a viscosity of 50-80 centipoise to prepare an inner coating, and then brush the inner coating on the surface of the aviation titanium forging to a thickness of 0.3mm, and air dry naturally; weigh Al2O3, TiO2, ZrO2 and CeO2 according to a mass ratio of 87:13:2:2, ball-mill them on a ball mill to form a powdery mixture, spray-dry the ball-milled powder to form a plasma-sprayed powder form, heat-treat and plasma-treat the spray-dried powder respectively, and the particle size is 20-50 microns, and finally plasma spray the aviation titanium forging brushed with the inner coating, with a spray thickness of 0.3mm, and air dry naturally to form an intermediate coating; then weigh B2O30.7%, Al2O336%, SiO230%, KOH 23.3%, TiB2 10%, then mix, and ball mill on a ball mill to form a powdery mixture with a particle size of 350-450 mesh; then add varnish and banana water, stir to a viscosity of 50-80 centipoise, brush on the outer surface of the intermediate coating with a thickness of 0.3mm, and dry naturally to complete the treatment of aviation titanium forgings.

Citation Information

Patent Citations

  • Aviation TC4 titanium plate coating and method for treating titanium plate

    CN102675952B

  • Aviation TC4 titanium plate coating and method for treating titanium plate

    CN102675952A

  • Composite ceramic coating for insulating bearing of wind driven generator and preparation method of composite ceramic coating

    CN113549859A

  • Protecting composite material parts against oxidation

    US20030194574A1